2018
DOI: 10.1186/s12936-018-2569-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of malaria parasitaemia with peripheral blood monocyte to lymphocyte ratio as indicator of susceptibility to severe malaria in Ghanaian children

Abstract: BackgroundEven though malaria is generally on the decline due extensive control and elimination efforts, it still remains a public health problem for over 40% of the world’s population. During the course of malaria infection, parasites and red blood cells come under oxidative stress and there is host immune response in an attempt to protect the red blood cells. The frequency of monocytes and lymphocytes in peripheral blood might, therefore, be expected to reflect the state of an individual’s immune response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
(28 reference statements)
9
15
0
Order By: Relevance
“…A mathematical model study also designated good relationships of the parasite density with neutrophil, lymphocyte, monocyte, and eosinophil count in P. falciparum infection [17]. Despite those discordances, insignificant correlations of parasite density, in both species, with hemoglobin concentration, leukocyte count, and monocyte count, in this study, agree with the previous studies [3], [7]. Interestingly, the positive correlation of eosinophil count and parasite density in P. vivax group seems becoming a new finding referring to those studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A mathematical model study also designated good relationships of the parasite density with neutrophil, lymphocyte, monocyte, and eosinophil count in P. falciparum infection [17]. Despite those discordances, insignificant correlations of parasite density, in both species, with hemoglobin concentration, leukocyte count, and monocyte count, in this study, agree with the previous studies [3], [7]. Interestingly, the positive correlation of eosinophil count and parasite density in P. vivax group seems becoming a new finding referring to those studies.…”
Section: Discussionsupporting
confidence: 89%
“…These results appear contrary to some studies that indicated several significant correlations. An inverse correlation between the parasite densities with the lymphocyte count in P. falciparum infection and positive correlations of the parasite density with neutrophil and platelet counts in P. vivax and P. falciparum infection were reported by studies in Ghana and South Ethiopia [3], [7]. A mathematical model study also designated good relationships of the parasite density with neutrophil, lymphocyte, monocyte, and eosinophil count in P. falciparum infection [17].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…4E ). The monocyte to lymphocyte ratio has been used as a marker of infection in a range of diseases ( 54 56 ), including malaria, where positive correlations with parasitemia and severe disease have been noted ( 57 , 58 ). Relative to controls, monocyte to lymphocyte ratios were significantly increased by day 4 p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Falciparum malaria associated with several hematological changes that involve the major blood cell lines such as red blood cells, white blood cells and platelets (6,7), which play a significant role in severity of falciparum malaria (8,9). Malaria hematological changes arising from hemolysis, host immune (inflammatory) response, bone marrow suppression, and splenic pooling (10).…”
Section: Introductionmentioning
confidence: 99%